MEASURING THE IMPACT OF DIGITAL TECHNOLOGY ON ENHANCING E-COMMERCE IN ALGERIA COMPARED TO A GROUP OF ARAB COUNTRIES (2010-2023) - Daoudi, Abdelfettah; Balouz, Mohamed; Bouakel, Mustapha; Abada, Abderraouf (Socio-economic relations in the digital society, 2025)
This study explores the influence of digital technology on the growth of e-commerce in Algeria compared to selected Arab countries—Tunisia, Egypt, Saudi Arabia, and the United Arab Emirates—over the period 2010 to 2023. It examines the role of key technological advancements, including the Internet of Things (IoT), artificial intelligence (AI), machine learning, digital payment systems, and big data analytics, in shaping the expansion of business-to-consumer (B2C) e-commerce. Using an econometric approach, the study employs panel models and analyzes the outputs generated by the EVIEWS 12 software. After conducting selection tests, the analysis determined that the fixed effects model is the most suitable for capturing the underlying relationships within the dataset. The study concluded that a strong and positive correlation exists between the adoption of modern technologies and the evolution of e-commerce. Among these technologies, artificial intelligence and machine learning emerged as pivotal drivers of growth in this sector. Following closely in significance, the Internet of Things (IoT) plays a crucial role in enhancing the operational efficiency of connected devices. Additionally, the study underscored the importance of e-wallet technology and big data analysis, albeit to a relatively lesser extent, in facilitating and optimizing electronic transactions. These insights highlight the necessity of reinforcing digital infrastructure, advancing AI-powered solutions, and broadening the adoption of digital payment technologies to accelerate e-commerce development in Arab economies.